PERSEPSI ORANG TUA TERHADAP KARAKTER KERJA KERAS SISWA SELAMA BELAJAR DI RUMAH: SEBUAH PENELITIAN DI KELAS V SDN 147 PEKANBARU - Nur Chayani; Eddy Noviana; Zetra Hainul Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reviews the parents' perception of the character of students' hard work during study at home in class V of SDN 147 Pekanbaru. The research described in this article was conducted at SDN 147 Pekanbaru, which is located at Anggrek 2 Garuda Sakti Street Km. 2 Tampan Pekanbaru in Riau Province in the academic year of 2021/2022. The research was quantitative descriptive research. The population obtained from the study was the parents of class V students in SDN 147 Pekanbaru, which consisted of four classes with 88 students. The sample determination technique in the study used saturated sampling techniques as the number of samples used was 88 parents of students. Data collection techniques used questionnaires and documentation. Data analysis techniques were used through validity tests and reliability tests. The results showed that 1) parents' perception of students' hard work during the study at home based on the work classification on the indicator of completing tasks well and on time, the percentage of achievement that obtained the category of very hard working as a teacher was 88.99%, whilst the percentage of achievement of self-employed and housewives obtained the category working hard were 80.23% and 79.47%. 2) The perception of parents on the indicators of not giving up easily in completing tasks, the percentage of achievements that obtained the very hard-working category as entrepreneurs were 83.49% and 86.01% as teachers, while housewife obtained a hard-working category was 80.82%, and 3) the overall perception of parents towards students' hard-working while studying at home in class V of both indicators obtained a very good or very hard-working category.